POTRET TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH (TPKD) DI INDONESIA - Syamsul Syamsul (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study aimed to describe the transparency level of regional financial management (TPKD) in Indonesia, as in the Presidential Instruction (Inpres RI) No. 7 of 2015 on Actions to Prevent and Eradicate Corruption. This research was conducted in 138 local governments (Pemda), and the data was the regional financial management for 2019 fiscal year. The results showed the average TPKD index is 24.36 percent which was achieved by the Provincial Government, while the average index for the City and Regency Government is not very different. Meanwhile, Java regional governments received higher average scores than other regions, but no significant differences. Therefore, these findings showed the TPKD level of Local Governments is very low and can be said to be non-transparent.